Tram-train system as a potential transport solution for the Olomouc Region - Metelka, Stanislav; Janoš, Vít (Transport, 2024)
The article is focused on the frequently discussed topic of suburban and regional railway system modernization comparing different approaches to consider by local authorities. To make a precedent and to better contribute to practical problems, a middle-sized city of Olomouc (Czechia) is chosen to demonstrate the upgraded regional transport system design with respect to the regional specifics and utilizing of the current railway and tramway infrastructure. With a new, innovative approach to the potential tram-train implementation in the Olomouc Region, the technical and operational features of the current tram-train systems and vehicles are analysed. By implementing the most suitable ones, the regional tram-train system proposal in the conditions of Olomouc may serve as a guide for similar planned systems in the countries with limited legislative and technical experience regarding the tram-train systems (especially in Central Europe), their suitability for the region, their design, and introduction. For the qualitative assessment of the different relevant approaches, a comparative analysis is used. As a result of the analysis, a tram-train system is recommended for the further transport planning stages as it significantly improves both urban and suburban public transport in the Olomouc Region by increasing their average speed and accessibility. For better financial and technical implementation, the project is divided into several stages. Unlike the already presented solutions, it combines shorter travel times of the regional rail and the populated area coverage reached by regional buses and serves as both an attractive and financially sane extension of a regional public transport system.